Electronic Banking in Opinion of Young Customers in Poland - Elzbieta Wyslocka; Dorota Jelonek (International Journal of Informatics and Information Systems, 2019)
The paper presents theories regarding the characteristics of consumer behavior of young customers on the basis of relevant literature and development of electronic banking in the world and in Poland. Then the methodology of conducted study and results have been described. At the end there is a summary, which presents recommendations for both practitioners and academics. Aim of this article is to determine the attitude of young consumers towards electronic banking based on a survey among the group of selected students. This seems especially important because current young consumers are increasingly better educated and are able to determine their needs very precisely. They access information quickly which enable them to determine whether the offer meets their expectations-banking services are no exception. Results of studies may help both the bank management to formulate marketing strategies to promote virtual banking and scientists in the study of virtual banks and virtual organizations in general.